ORGANIZATIONAL AND PEDAGOGICAL CONDITIONS OF E-LEARNING COURSE USING IN THE HIGHER EDUCATION PROCESS IN UKRAINE - Бобрицька, В. І.; Процька, С. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article is substantiated the pedagogical conditions for the e-learning course using (ELC) in the educational process of the Ukrainian higher education institutions (HEI). There had been found out that systemic, competent, personality-oriented and activity-based approaches are common in the HEI, that indicated the priority orientation in the development and using of the ELCs for complexity, practical orientation, personification in the organization of the educational process. The peculiarity of the selection of pedagogical conditions for the application of the ELC is emphasised on the formation of information and computer literacy, value guidance, cognitive interest in future specialists of different specialties, due to the specificity of their professional training. The research methods are applied some logic and structural analysis for the structure determining of construction of ELCs on the MOODLE platform in HEI; analytical-system method, pedagogical experiment for substantiation and determination of pedagogical realization expediency of pedagogical conditions in the process of using ELC during professional training of different-specialty students in HEI The structure of the ELC "Educational Policy" (National Dragomanov National Pedagogical University) and "General Pedagogy" (Boris Grinchenko University of Kyiv) on MOODLE platform for students of specialty 01 “The Educational Sciences” has been characterized. In view of the practical experience of designing and using the studied ELCs, the following structure is didactically logical: an IT course; a lecture course; some assignments for seminars and practical classes; an independent-working unit; a block of final progress tests for students etc. The improving the content recommendations of the ELC are offered. The pedagogical realization expediency of certain conditions in the process of vocational students training in educational and professional programs for the speciality “The Educational Sciences”01 Education / Pedagogy and 03 Humanities was experimentally investigated. The analysis of the results of pedagogical experiment on the efficiency of the using of ELC is presented, which testifies to the increase of the level of professional competence formation of the HEI-studied students